HARNESSING THE POWER OF PROTOTYPING METHOD FOR ENGAGING RESPONSIVE WEB PROFILES - Ananto Tri Sasongko; Sunita Dasman (JIKO (Jurnal Informatika dan Komputer), 2023)
This research discusses the implementation of the prototyping method in enhancing institutional visibility through the development of responsive web profiles. Institutional visibility is key to achieving success and sustainable growth in today's digital era. Developing a responsive web profile increases visibility by providing optimal user experience across various devices and screen resolutions effectively. The prototyping method was the primary approach in developing this responsive web profile. It allows developers to create initial models that can be tested and evaluated before the full development of the web profile. The research explains the steps in developing a responsive web profile using prototyping. The results show that this method offers an efficient and practical approach to creating a responsive web profile, ensuring user satisfaction, and meeting the increasing expectations of users. Therefore, institutions should consider applying this prototyping method to strengthen their visibility through innovative, responsive web profiles. Responsive web profiles enable institutions to reach and engage their target audience through different devices, enhancing user engagement and providing consistent user experiences. The result shows that prototyping enhances institutional web profiles, improves user experience, and effectively increases visibility with high satisfaction, with an average of 83.2.